(untitled) (Eureka Journal of Business, Economics & Innovation Studies, 2026)
This article examines the fundamental role of the digital economy in the modern development of business entities. It explores digital transformation models, the integration of Big Data, and the shift from traditional commerce to digital platforms. Using a qualitative analysis of global trends, the research highlights how digital tools such as AI, machine learning, and cloud computing reduce operational costs and improve customer engagement. The findings suggest that for developing economies like Uzbekistan, a structured digital strategy is essential for maintaining global competitiveness.